Eighteenth-Century Western Cree and Their Neighbours - Russell, Dale R. (Book collections on Project MUSE., 1991)
The author discusses the history of the Cree and Assiniboin in the early 1700s by examining eighteenth century historical documents, which fail to support the accepted view that the Cree and Assiniboin invaded the west after 1690 as a result of the introduction of the fur trade.